2021
DOI: 10.1016/j.ijcha.2021.100871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron supplementation in patients with heart failure and iron deficiency: A systematic review and meta-analysis

Abstract: Background The effectiveness of oral and intravenous iron supplementation in reducing the risk of mortality and hospitalizations in HF patients with iron deficiency is not well-established. Methods A thorough literature search was conducted across 2 electronic databases (Medline and Cochrane Central) from inception through March 2021. RCTs assessing the impact of iron supplementation on clinical outcomes in iron deficient HF patients were considered for inclusion. Prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…In HF hearts, the highest number of significant correlations (p < 0.05) we found for: DMT-1 (11); L-CH (10); and TfR-1, FT-H, ACO-1. The highest number of moderate/strong correlations r ≥ 0.5, p < 0.05 we found for L-CH (4). The main correlations between iron transport, storage and regulatory proteins were positive, except hepcidin, which was negatively correlated with L-CH and FPN.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…In HF hearts, the highest number of significant correlations (p < 0.05) we found for: DMT-1 (11); L-CH (10); and TfR-1, FT-H, ACO-1. The highest number of moderate/strong correlations r ≥ 0.5, p < 0.05 we found for L-CH (4). The main correlations between iron transport, storage and regulatory proteins were positive, except hepcidin, which was negatively correlated with L-CH and FPN.…”
Section: Discussionmentioning
confidence: 67%
“…Several studies and clinical trials have demonstrated that iron supplementation in HF patients has improved their quality of life and functional capacity, significantly reducing the risk of first hospitalization and hospital readmissions, and improving peak oxygen consumption and functional capacity (measured by a 6-min test walk) [17]. However, some of cardiologists question the beneficial role of iron supplementation in the course of HF, pointing to the lack of significant improvement in the patient's condition or lack of reduction in the risk of cardiovascular death [4,18]. Moreover, iron overload by supplementation is toxic to the organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent meta‐analysis conducted by Yamani et al . 30 separately examined oral and IV iron supplementation and found that IV iron‐carbohydrate supplementation significantly reduced overall and HF hospitalizations compared with control. Consistent with these previous meta‐analyses, the present study found that IV iron‐carbohydrate therapy reduced the rates of hospitalization for worsening HF and also first hospitalization for worsening HF or death, but did not significantly alter the rate of all‐cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…of RCTs including patients with HF, regardless of LVEF, found that iron supplementation (oral or IV) improved HF hospitalization rates, cardiac function, and QoL, but did not impact on mortality rates. A more recent meta‐analysis conducted by Yamani et al 30 . separately examined oral and IV iron supplementation and found that IV iron‐carbohydrate supplementation significantly reduced overall and HF hospitalizations compared with control.…”
Section: Discussionmentioning
confidence: 99%